Comparisons of Perceived Training Doses in Champion Collegiate-Level Male and Female Cross-country Runners and Coaches over the Course of a Competitive Season - Kyle R. Barnes (SpringerOpen, 2017)
Abstract Background Session rating of perceived exertion (sRPE) is a practical tool for coaches to assess internal training load of their athletes. In a sport like cross-country running, that is individual in nature, but has a team training and competition component, information about the association between external and internal load is lacking. Furthermore, there is a need for studies that examine perception of training doses across multiple training cycles including the competitive season as well as between male and female athletes. Methods Session RPE, duration, and training load (TLRPE = sRPE × duration) of 25 highly trained male and female cross-country runners and their coaches were recorded for every training session (110 days) throughout a collegiate cross-country season. Intensity (sRPE), duration, and TLRPE were compared between coaches and runners by gender separately. Training sessions were also analyzed by those intended by the coaches to be easy, moderate, and hard as well as by training period. Results Data from 3024 training sessions were collected, 62% of which were considered "easy," 18% "moderate," and 20% "hard." Men and women rated coach-intended easy sessions significantly harder during each month of the season (effect size (ES) > 2.9, p < 0.0001). Men rated moderate intensity sessions significantly higher than coaches (ES ≥ 1.0, p ≤ 0.002), whereas females rated hard intensity sessions significantly lower than coaches (ES > 0.5, p < 0.008). There was no difference between males and coach's hard sessions (ES < 0.07, p > 0.05) or females and coach's moderate sessions (ES < 0.18, p > 0.05). Training intensity and TLRPE tended to increase throughout the season (p > 0.05), with a significant increase in moderate and hard intensity sessions in the last training period (p < 0.001). Conclusions The results indicate the male and female cross-country runners tend to regress to moderate intensity training throughout the cross-country season. Given the success of the athletes in this study, these results show how a simple system for monitoring training such as the sRPE method may improve control of training variables and provide a useful tool for coaches to evaluate training load placed on athletes in a simple, responsive way.